Pengaruh Latihan Push Up Terhadap Kekuatan Pukulan Oi-Tsuki Chudan Karate Dojo SMA Negeri 2 Kerinci (Inkanas) - Romiya Heliza; Agnes Fetiloka (Jurnal Ilmiah Wahana Pendidikan, 2023)
The purpose of this study was the effect of push-up exercises on the punching power of oi-tsuki chu and karate dojo at SMA Negeri 2 Kerinci (Inkanas). This research was conducted in the form of experimental research, with experimental methods. The subject of the study was the Karate Dojo of SMA Negeri 2 Kerinci (Inkanas), with a total of 10 participants. The instrument used is the power of the oi-tsuki chudan punch. Data analysis techniques using hypothesis testing with t test analysis (paired sample t test). Based on the results of the pretest and posttest analysis, it means that there is an effect of push up training on the strength of the oi-tsuki chudan punch. With the amount of influence given by 40%. Based on these results, it can be concluded that there is an effect of push-up training on the strength of the oi-tsuki chudan karate dojo SMA Negeri 2 Kerinci (Inkanas) and the percentage increase in strength with push-up exercises has a greater increase.